2006
DOI: 10.1159/000097127
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 and Monocyte Chemotactic Protein-1 mRNA Expression in Perinatally Infected and Asphyxiated Preterm Neonates

Abstract: Background: Inflammation due to perinatal infection (PI) and perinatal asphyxia (PA) may cause damage to various tissues and very often to the immature brain of the fetus and the newborn. Previously, we have shown that the neonatal immune system has the ability to produce increased chemokine protein levels in the serum during the inflammatory response caused by PI and PA. Aim: The aim of our present study was to investigate mRNA levels of the proinflammatory chemokines interleukin-8 (IL-8) and monocyte chemota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…These multiple function secondary mediators cause activation of the coagulation cascade, the complement cascade, as well as participate in the production of prostaglandins, leukotrienes, proteases, and oxidants. As a result of these highly regulated factors, most adverse effects of sepsis such as SIRS, disseminated intravascular coagulation (DIC), septic shock, multiple organ dysfunction syndrome, and complement activated response syndrome are associated with an imbalance in the production of proinflammatory mediators [84][85][86][87] as well as the counterbalance synthesis of anti-inflammatory cytokines. Anti-inflammatory cytokines include IL-4, IL-10, tumor necrosis factor soluble receptor, IL-1 receptor alpha, and transforming growth factor beta 2 (TGF-β2).…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%
See 2 more Smart Citations
“…These multiple function secondary mediators cause activation of the coagulation cascade, the complement cascade, as well as participate in the production of prostaglandins, leukotrienes, proteases, and oxidants. As a result of these highly regulated factors, most adverse effects of sepsis such as SIRS, disseminated intravascular coagulation (DIC), septic shock, multiple organ dysfunction syndrome, and complement activated response syndrome are associated with an imbalance in the production of proinflammatory mediators [84][85][86][87] as well as the counterbalance synthesis of anti-inflammatory cytokines. Anti-inflammatory cytokines include IL-4, IL-10, tumor necrosis factor soluble receptor, IL-1 receptor alpha, and transforming growth factor beta 2 (TGF-β2).…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%
“…As the circulating concentrations of inflammatory markers such as the cytokines, chemokines, and acute phase reactants may not fully represent the complete host response to an infection, these technologies push researchers to focus on chemokine mRNA expression and its relation to infection and other stressors such as birth asphyxia. 11,85 Recent reports demonstrate an association of elevated IL-8 mRNA expression in neonates exposed to perinatal infection compared to mRNA expression of IL-8 and MCP-1 expression changes in neonates with perinatal asphyxia. 85 Proteomic and metabolomics profiling technologies provide insight into the functional expression of proteins or metabolites present in a biological sample.…”
Section: Use Of Other Body Fluids In Diagnosis Of Neonatal Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…One study measuring whole blood IL-8 and MCP-1 mRNA concentrations suggested that levels of both mRNAs were elevated in infants with perinatal asphyxia, whereas only IL-8 mRNA level was elevated in infants with perinatal infection. 47 The detection of tissue-specific mRNA could potentially be used as a basis for developing disease-specific biomarkers in neonates.…”
Section: Genomicsmentioning
confidence: 99%
“…FIRS is also associated with an increase in fetal plasma concentrations of soluble tumor necrosis factor receptors-1 and 2, IL-1β, IL-8 and C-reactive protein [310]. FIRS is associated with the impending onset of preterm labor/delivery, microbial invasion of the amniotic cavity and increased perinatal morbidity after adjustment for gestational age [1124].…”
Section: Introductionmentioning
confidence: 99%